PENGARUH PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MENULIS DAN BERBICARA SISWA DI SMAN 7 DENPASAR - Putu Gede Ananta Wiguna (Lembaga Pengembangan Kinerja Dosen, 2024)
This study intends to: (1) Analyze the effect of the implementation of PjBL on students' Writing achievement in SMAN 7 Denpasar. (2) Analyze the effect of the implementation of PjBL on students Speaking achievement in SMAN 7 Denpasar. (3) Find out students’ perceptions about implementing Project-Based Learning in the influence of writing and speaking classes in SMAN 7 Denpasar. The Design and Development model by Pardede (2019) serves as the foundation for the methodology of this study. The three phases of the design and development model are observations, experiment, design, and analysis. Instruments such as learning scenarios, documents, and questionnaires were utilized to collect data for this study. Miles & Huberman (2013) examined the data statistically and qualitatively. The research reveals that: (1) The implementation of PjBL significantly increases students' writing and speaking achievement, increases students' active participation, and teamwork, and (2) there is an increase in student learning outcomes after participating in project-based learning. Based on the values obtained, the average post-test scores increased learning outcomes, (3) project-based learning was very positive because it had an impact on students such as thinking more critically and systematically in completing assignments, becoming more active, learning more interactive, providing opportunities for students to manage their activities or activities to complete assignments to train themselves to be independent.